Determining Bedrock Quality by Geoelectric Method: A Soil Investigation Study in Moramo District, South Konawe Regency, Indonesia - Tachrir Tachrir (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
In comparison to the findings of deep drilling, this study tries to describe the depth of bedrock and soil layers. Wawatu Village, North Moramo District, South Konawe Regency, Southeast Sulawesi Province, Indonesia, served as the location for data collection. Kendari City is 30 kilometers away from the settlement. The community has three borders: the Sea to the east, Wawatu community to the south, and Tanjung Tiram Village to the north. Additionally, it shares a boundary with Abeli Village to the west. The settlement of Wawatu is located at 40 3' 35" S, 1220 38" 52" T, and 0 m above sea level. Res2dinv software uses data processing and interprets it to produce the 2D Pseudo section. based on modeling of 2D resistivity, It is evident that there are three underground rock layers in Wawatu Village, North Moramo District, and South Konawe District. The resistivity measurement is greater than 10 m, indicating bedrock at a depth of 10–18 m.    the category of sandy loam layer for soil quality. This implies that the pile foundation's depth is based on the depth of such soil.